Community Empowerment Through the Utilization of Used Oil-Fueled Stove Technology as an Effort Toward Energy Independence: Pemberdayaan Masyarakat Melalui Pemanfaatan Teknologi Kompor Berbahan Bakar Oli Bekas Sebagai Upaya Menuju Kemandirian Energi - Ibnu Irawan; Hairil Budiarto; Ach. Dafid (DPD Jatim Perkumpulan Dosen Indonesia Semesta, 2025)
Poreh Village, Lenteng District, Sumenep Regency, faces challenges in accessing efficient and affordable energy, while the use of conventional energy sources has negative impacts on both the environment and the economy. This community service program aims to empower the residents of Poreh Village, by utilizing waste oil-powered stoves as a means to reduce dependency on unsustainable energy sources such as firewood and LPG. This program involves several stages, including introducing the technology, installing stoves in pilot households, training on waste oil management, and monitoring the effectiveness of stove usage. The program results indicate that the community understands the technology and can use it effectively. The adoption of waste oil stoves reduces dependency on conventional fuels, achieving up to 40% in energy cost savings and a decrease in carbon emissions. This program is expected to have a long-term impact, including increased energy independence, emission reductions, and the creation of economic opportunities through waste utilization. The active involvement of the community and students is also a key factor for the program's sustainability in the future.